Effect of E-Service Quality on Customer Satisfaction and Word of Mouth on Online Shopee in Morowali Regency - Mohammad Zeylo Auriza; Mahfud Supu; Syamsul Bachri; Citra Antasari; Salma Daud (Institute of Computer Science (IOCS), 2022)
In today's development, many companies in any business industry compete so tightly because companies are more careful and creative in developing ideas that are poured into competitive strategies through technology and information. Many companies that have started implementing an online transaction system have responded positively to customers who prioritize efficiency and effectiveness in shopping. One of the developing marketplaces in Indonesia is Shopee. Shopee became the top online shopping platform in Indonesia in the first half of 2021, from January to mid-year, in terms of the total number of app downloads and total monthly active users based on research by mobile app market researcher Annie. This study aims to determine the effect of e-service quality on customer satisfaction and Word Of Mouth online Shopee in Morowali Regency by using the Amos Software analysis tool. 21.0. The results of this study indicate that the e-service quality variable has a positive and significant effect on Shopee online customer satisfaction, the e-service quality variable has a positive and significant influence on the word of mouth of Shopee online customers and the customer satisfaction variable has a positive and significant effect on the word of mouth variable. online shopee customers in Morowali Regency.